Design of a Low Consumption Electric Car Prototype - Fonte, Carlos Magno dos Reis (2015)
Concerned with environment and sustainability, Shell has organized for the last 30 years a competition of energy efficient road vehicles called Shell Eco-Marathon (SEM). The vehicle is required to achieve a minimum mean cruise speed of 25km/h and a low drag value is an essential parameter to achieve a good result. Over the years SEM teams used a streamlined body similar to an airfoil with a minimized low frontal area, however AERO@UBI team decided to create a new concept vehicle body. This 3D body also derives from a 2D airfoil, but a geometric transformation introduced by Galvão in 1968 in "Nota técnica sobre corpos fuselados", São José dos Campos, for the creation of low drag fuselage is used. According to that author, it is possible to replicate the pressure coefficient distribution of the airfoil in the 3D body. Thus, maintaining the airfoil's low drag characteristics. Through the use of CFD software ANSYS Fluent it was possible to confirm the used concept and examine the vehicle aerodynamic. Although the final result was not optimal, it was possible to confirm the theory introduced by Galvão. [...]